IMPROVING VOCABULARY MASTERY BY USING TALKING STICK METHOD TO THE EIGHT GRADE STUDENTS OF MTS ANNAJAH PETALING - Hartati Hartati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
The objectives of this research was to find out whether or not there was any significant difference in vocabulary mastery between students who were taught by using talking stick method or students who were taught without using talking stick method. The research was limited on word classes consisted of noun, adjective and verb in descriptive texts with the topic of the material was animal, people, thing, and places.This research was conducted by using quantitative method with a quasi-experimental group design. The experimental group students were taught by using Talking Stick method, while the control group students were not taught by using Talking Stick method. The samples were 74 students that were taken from the eight grade students of MTs Annajah Petaling in academic year 2015/2016. The data were obtained through test, observation and documentation. The result of the test was analyzed by using paired sample t-test in SPSS 16 (Statistical Package for Social science).Based on the results analysis, there was a significance different between students who were taught by using Talking Stick method and the students who were not taught by using Talking Stick method. It was known from the result of mean of post-test in the experimental group (67.70) was higher than the mean of post-test in the control group (65.54). In addition, there was a significant difference in vocabulary mastery between students’ who were taught by using Talking Stick method and those who were not. Therefore, Talking Stick method was one of effective factor that could improve students’ vocabulary mastery.